The Incidence of Hypertension in Internal Polyclinic in Latemmamala Hospital Soppeng - Ida Leida Maria; Maftur Al Rafi; Rismayanti Hafidz; Firman Firman (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Hypertension, otherwise known as high blood pressure, is a condition that describes blood pressure significantly in the interval above 140/90 mmHG, which results in the death of 9.4 million people every year worldwide, with the incidence of the problem increasing over time. According to WHO, it is predicted that 1.28 billion or about 42% of people worldwide are diagnosed with hypertension, and the results of the 2018 Riskesdas suggest that the prevalence of hypertension in Indonesia increased to 34.1% from 25.8% in 2013. The type of research used is analytic observational with a cross-sectional study approach. The population in this study were all visitors recorded in the Internal Medicine Clinic register book at Latemmamala Hospital from January to December 2021, namely 707 people. The sampling technique used was simple random sampling with a total sample size of 148 people. This study finds that nutritional status (p=0.002), total cholesterol levels (p=0.000), abdominal circumference size (=0.000), and family history (p=0.000) had a relationship with the incidence of hypertension. As well as, type of work (p=0.078), marital status (p=0.916), stress level (p=0.079), smoking habits (p=0.261), and physical activity (p=0.376) have no relationship with the incidence of hypertension. This study shows a relationship between nutritional status, cholesterol levels, abdominal circumference size, and family history of hypertension. It is highly recommended for people with hypertension adopt a healthy lifestyle, such as maintaining a diet and regular physical activity to keep their blood pressure under control.